Barriers and enabling factors for utilizing physical rehabilitation services by Afghan immigrants and refugees with disabilities in Iran: a qualitative study - Elaheh Amini; Manal Etemadi; Saeed Shahabi; Cornelia Anne Barth; Farzaneh Honarmandi; Marzieh Karami Rad; Kamran Bagheri Lankarani (BMC, 2024)
Abstract Introduction Individuals with a migrant background often underutilize physical rehabilitation services (PRS) compared to the host population. This disparity is attributed to various barriers, including limited access to information, language barriers, illiteracy, and cultural factors. To improve PRS utilization by Afghan immigrants and refugees in Iran, it is crucial to identify these barriers and enabling factors. In response, this study explored the barriers and enabling factors for utilizing PRS among Afghan immigrants and refugees with disabilities in Iran. Methods This qualitative study was conducted in Iran between January and March 2023. Participants were selected through convenient and snowball sampling. Individual, semi-structured interviews were carried out both in face-to-face and online formats. Data analysis occurred concurrently with data collection, using the directed content analysis approach. Results Findings from our research indicate that common barriers to PRS utilization among Afghan immigrants and refugees include insufficient insurance coverage, high service costs, expensive transportation and accommodation, limited knowledge about Iran's health system, inadequate awareness of available supports, restricted access to PRS in remote areas, impatience among PRS providers, fear of arrest and deportation, a lack of trust in modern treatments, stringent immigration rules, high inflation rates limiting the ability to pay for PRS, and limited social support. On the other hand, several enabling factors were identified, such as strengthening insurance coverage, utilizing the capacities of charities and NGOs, providing information about available services, promoting respectful behavior by healthcare providers towards patients, facilitating cultural integration, and increasing immigrants' awareness of available services and eligibility criteria. Conclusion The barriers and enabling factors uncovered in this study offer valuable insights into the complexities surrounding PRS utilization by Afghan immigrants and refugees with disabilities in Iran. Understanding and addressing these factors is essential for developing targeted interventions and policies that can improve access and utilization, ultimately leading to enhanced health outcomes for this vulnerable population.